L-arginine is an effective medication for prevention of endothelial dysfunction, a predictor of anthracycline cardiotoxicity in patients with acute leukemia - Skrypnyk, I.; Maslova, G.; Lymanets, T.; Gusachenko, I. (Experimental Oncology, 2017)
Aim: To evaluate the effectiveness of L-arginine in the prevention of endothelial dysfunction, which may be a predictor of anthracycline-induced myocardial injury, in patients with acute leukemia (AL) on the background of anthracycline antibiotics low cumulative doses from 100 to 200 mg/m2. Materials and Methods: A total of 81 adult AL patients (38 males and 43 females with the age of 16–59 years) were studied. The patients were divided into two groups: group I (n = 34), AL patients treated with chemotherapy (CT) and L-arginine hydrochloride; group II (n = 47) — AL patients treated with CT only. Cardiac evaluation and endothelial function assessment were performed at baseline and after second CT. Electrocardiography (ECG) parameters, lipid peroxidation activity, antioxidant protection and NO system state were evaluated. Results: The bioelectric activity abnormalities of the myocardium were observed in studied patients with low cardiac risk after induction CT. In case of L-arginine administration, only minimal daily ECG changes were recorded. A significant difference in the lipid peroxidation and antioxidant defense system activity in patients of groups I and II was determined. We noticed deepening of endothelial dysfunction on the background of cytostatic therapy with anthracycline antibiotics compared with baseline values in patients of group II. It was found that prophylactic L-arginine increases superoxide dismutase level and reduces the total NOS activity due to its inducible isoform. Conclusion: The leading factor of anthracycline-induced cardiotoxicity is the imbalance between free radical generation and their inactivation that leads to endothelial dysfunction development. L-arginine eliminates the prooxidant-antioxidant imbalance and improves the endothelial function.